Повышение электромагнитной совместимости частотно-токовых преобразователей с нагрузкой - Скурятин, Ю.В.; Денисевич, Н.А. (Технічна електродинаміка, 2012)
In this paper the converter of frequency of current with the output filter and zero-overshoot response operating mode is presented. The possibility to provide electromagnetic compatibility of converter and the load is shown.